Tuberculin sensitivity among inmates of children’s home - C. B., Usha Kiran; J., Sowmya; R., Jayamala (International Journal of Contemporary Pediatrics, 2017)
Background: Tuberculin sensitivity and its relationship to nutritional status in inmates of children’s home. Methods: Tuberculin sensitivity was checked in 180 apparently healthy orphan children and its relationship with nutritional status, previous vaccination status was studied. setting: children’s home run by NGOs participants: all inmates of children’s home aged 2-15 years who meet inclusion and exclusion criteria. Results: Out of 180 apparently healthy children 27 (15%) were tuberculin positive. 109 (60.5%) were undernourished children out of which 15 (55.56%) were tuberculin positive. Out of 71 normal nourished children, 12 (44.4%) were tuberculin positive. BCG scar was present in 120 (66.6%) children out of which 19 were tuberculin positive and BCG scar was absent in 60% children out of which 8 were tuberculin positive. 8 children had history of contact with TB and 6 of them were tuberculin positive. Conclusions: Tuberculin sensitivity testing using 5 TU PPD-RT23 is a simple feasible method to screen inmates of children home at the time of entry and it is not influenced by nutritional status or previous BCG vaccination. Early diagnosis and treatment of TB will go a long way in reducing the burden of TB in our country.